The Legal Impact of Merger, Acquisition, and Other Corporate Restructuring Activities on Employment Relationship Based on Labor Law in Indonesia After the Enactment of the Job Creation Law - Aziz Rahimy (Polit Journal Scientific Journal of Politics, 2023)
Mergers, acquisitions, and other corporate restructuring activities are regarded as one of the strategic steps to maintain the company's existence and to carry out business growth, which can be done when the company is in financial difficulties or when the company intends to develop its business and increase its revenue. However, there have often been problems in the past related to employment relations and other legal issues on employment law. This study aims to determine the legal impact of merger, acquisitions, and other corporate restructuring activities on employment relations based on employment regulation in Indonesia after enactment of Law concerning Job Creation. This study uses the normative juridical method with descriptive analysis characteristics. The results of the study show that in the event of a corporate restructuring activities, the employment relationship may continue as long as there is no termination of employment, whether it arises at the initiative of the employer or the employee. The law provides preventive as well as repressive protection for employees in the event of corporate restructuring activities.